Kanan School Brand Identity Design as Kanan Barbershop Longevity Brand - Rahmat Hidayat (Judikatif: Jurnal Desain Komunikasi Kreatif, 2026)
The increasingly competitive development of the barbershop industry demands that business actors have a strong and sustainable visual identity. Kanan Barbershop responds to this development through a barbering skills training program called Kanan School, as part of its brand longevity strategy, but until now Kanan School does not have a brand identity that is able to represent the character, values, and image of the program professionally and consistently. This study aims to design the Kanan School brand identity as an effort to strengthen the sustainability of the Kanan Barbershop brand. The method used in the design is artistic research with a qualitative approach through SWOT analysis and the glass box method. The design results in a visual identity designed to represent the values ​​of professionalism, education, creativity, and the spirit of growth through elements of a mascot, barberpole, and sunburst. This design is expected to strengthen the positioning of Kanan School as a barbering training program while supporting the sustainability of the Kanan Barbershop brand. Keywords: Brand Identity, Brand Longevity, Kanan Barbershop.